2000
DOI: 10.4269/ajtmh.2000.62.181
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of febrile morbidity and use of permethrin-impregnated bed nets in a malarious area II. Determinants of febrile episodes and the cost of their treatment and malaria prevention.

Abstract: Abstract. The objective of this study is to determine the effect of permethrin insecticide-treated bed net (PITN) use on the incidence of febrile episodes and on household malaria expenses in Benin. Over the course of one year, 208 randomly selected PITN user and non-user households were visited weekly to determine expenditures on febrile morbidity and its treatment, and to monitor spending on malaria prevention. Multivariate analyses were performed to distinguish the effects of PITN use from other important d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…This was also reflected by the wish of respondents to diminish the price of the ITN. This finding confirms the results from many observations in SSA countries where lack of sufficient funds was a main reason for not buying ITN [20,[29][30][31][32][33][34][35][36]. This observation supports the arguments of those in favour for free ITN distribution systems in SSA [9].…”
Section: Discussionsupporting
confidence: 90%
“…This was also reflected by the wish of respondents to diminish the price of the ITN. This finding confirms the results from many observations in SSA countries where lack of sufficient funds was a main reason for not buying ITN [20,[29][30][31][32][33][34][35][36]. This observation supports the arguments of those in favour for free ITN distribution systems in SSA [9].…”
Section: Discussionsupporting
confidence: 90%
“…While an earlier study from The Gambia found no correlation between wealth and bed net use (Aikins et al. 1993), more recent studies have reported significant financial barriers to their use (Rashed et al. 2000; Yohannes et al.…”
Section: Discussionmentioning
confidence: 95%
“…1995). In poorer rural areas, traditional methods, such as burning local herbs, are more common (Rashed et al. 2000; Nuwaha 2002; Oguonu et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations